2012
DOI: 10.4238/2012.november.29.1
|View full text |Cite
|
Sign up to set email alerts
|

Hsp110 expression changes in rat primary myocardial cells exposed to heat stress in vitro

et al.

Abstract: ABSTRACT. We investigated and described the kinetics of heat shock protein (Hsp) 110 expression and distribution in rat primary myocardial cells exposed to heat stress in vitro. After incubation at 37°C for 72 h, myocardial cells were heat stressed at 42°C for 0, 10, 20, 40, 60, 120, 240, 360, and 480 min. Significant increases in aspartate transaminase, lactate dehydrogenase, and creatine kinase enzymatic activities in the myocardial cell culture media were observed during heat stress, suggesting that the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Cardio-specific marker enzymes have been shown to be released from the heart into the blood stream during myocardial damage because of degeneration of myofibrils and myocytes (Senthil et al, 2007). An in vitro study showed significantly increased enzymes such as AST, LDH, and CK in the culture medium of primary rat myocardial cells, suggesting that the integrity of these cells was altered because of heat stress (Liu et al, 2012). Our results showed that diagnostic marker enzymes clearly were elevated.…”
Section: Discussionmentioning
confidence: 50%
“…Cardio-specific marker enzymes have been shown to be released from the heart into the blood stream during myocardial damage because of degeneration of myofibrils and myocytes (Senthil et al, 2007). An in vitro study showed significantly increased enzymes such as AST, LDH, and CK in the culture medium of primary rat myocardial cells, suggesting that the integrity of these cells was altered because of heat stress (Liu et al, 2012). Our results showed that diagnostic marker enzymes clearly were elevated.…”
Section: Discussionmentioning
confidence: 50%
“…In addition, heat shock protein A4 ( HSPA4 ), a member of the HSP110 family, can control apoptosis of inflammatory cells and immune reactions in the gut [ 52 ]. In Liu et al’s study, it was found that the expression of Hsp110 in primary cardiomyocytes in vitro was sensitive to heat stress, and Hsp110 participated in the potential acquisition of heat tolerance after heat stress [ 53 ]. Therefore, these genes may be related to heat tolerance in Chinese local pigs, providing guidance for further exploration of heat tolerance genes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the mitochondrial membrane potential and the intensity of calcium fluorescence, which were testing indexes in the present study, play an essential role in the mitochondrial function of myocardial tissue homeostasis ( Skarka and Ostadal, 2002 ; Dibb et al, 2007 ; Kadenbach et al, 2011 ; Davlouros et al, 2016 ; Zorova et al, 2018 ; Schartner et al, 2019 ; Lai and Qiu, 2020 ). Understanding of the electrophysiological effects in cardiomyocyte contractile and mechanical function in response to cardiotoxic drugs has previously relied on primary cardiomyocytes from animal models ( Liu et al, 2012 ; Tang et al, 2016 ; Blair and Pruitt, 2020 ). Therefore, this research selected the abovementioned indexes to quantify the myocardial cytotoxicity of evodiamine and rutaecarpine in an effort to understand how these bioactive compounds of Euodiae Fructus directly impact the cGMP-PKG pathway at the cellular and cardiomyocytes levels.…”
Section: Discussionmentioning
confidence: 99%